Comparing Acala Defoliation Timings with Yield and Quality. Issue 1 (23rd January 2013) - Wright, Steven D.; Hutmacher, Robert B.; Banuelos, Gerardo; Roberts, Bruce A.; Munk, Daniel S.; Wilson, Katherine A.; Rios, Sonia I.; Hutmacher, Kelly A.; Keeley, Mark P.; Wrobles, Jonathan F.
Abstract : Chemical defoliation is a necessary pre‐harvest practice in cotton (Gossypium hirsutum L.) production in California, and all harvest aid efforts require proper timing to preserve cotton lint yield and quality. Generally, cotton growers are advised to begin defoliation as early as possible, but not so early that they cause yield and quality loss. In order to have confidence in this final pre‐harvest step, growers monitor the growth stage of their crop by counting the number of nodes above cracked boll (NACB). In California, it is common practice to apply the first defoliant treatment at 4 NACB, which corresponds with the US Cotton Belt's recommended timing, which is when 60% of the harvestable bolls are open (9, 20). It can be beneficial to have an early defoliant application because often it leads to an earlier harvest. This early harvest allows cotton growers to conduct their harvest prior to the onset of adverse late‐season fog or rains that can occur in California's San Joaquin Valley and make harvests more difficult. The objective of this research on San Joaquin Valley Acala cotton was to compare the impact of different rates of Ginstar (thidiazuron/diuron) or Ginstar plus Finish (ethephon/cyclanilide) on defoliation, yield, and fiber quality of cotton when defoliant applications were initiated at the earlier 6 NACB timing, which corresponds to 40% open boll versus the common 4 NACB timing. Starting the defoliation process with an Acala cultivar at 6 NACB instead of at 4 NACB did not significantly affect yield or cotton HVI (high volume instrument) fiber quality characteristics. Earlier defoliation could be of significant benefit in years when later‐maturing crops or worsening harvest‐season weather necessitate the initiation of an earlier harvest.